Putting a face on the dark figure: Describing victims who don’t report crime - Fohring Stephanie (Temida, 2014)
Since the inception of large scale victimisation surveys a considerable amount of research has been conducted investigating the so called ‘dark figure’ of unreported crime. Although this figure has consistently hovered around 60% of all victims, recent research reveals little about those who choose not to pursue formal avenues of justice. This article thus seeks to open a dialogue which focuses on the actual people behind the dark figure. It uses examples from the Scottish Crime and Justice Survey to describe these individuals and to explore explanations for their non-reporting. It highlights the importance of deprivation and vulnerability with regards to reporting crime but also the initial risk of victimisation. It concludes by arguing that the lack of focus on victims who don’t report leaves them vulnerable and invisible to the eyes of policy makers and the criminal justice system.